PENINGKATAN KUALITAS SISWA TERAMPIL IPTEKDENGANEDUKASIKOMPUTERBAGI SISWASDDI DUSUN WONOLELO - Budi Agus Riswandi (Asian Journal of Innovation and Entrepreneurship, 2013)
In the era of globalization, education experiencing tremendous change. Currently,teachers are not the sole source of knowledge for students. The advent of the internetand electronic media students can access easily lead students can learn anywhere andanytime without having to be accompanied by a teacher. Thus, education should alsoadjust the technology has to happen today. Schools in Indonesia to implementtechnology-based education using the computer as a medium of learning in schools. Buton the other hand, it requires schools to have the infrastructure to support theimplementation of technology-based learning. For schools that do not have theinfrastructure to support it can not implement technology-basededucation. This is onereason technology-based learning has not applied optimally in Indonesia. SD Jambewangiincluding schools that did not have the infrastructure to support learning computer skillsso they are left in the process of learning the use of science and technology even mosttechnology illiterate. with the holding of the computer education program is expected toenhance the skills and knowledge of children about the importance and usefulness ofcomputers so that students in elementary Jambewangi not lagging behind in the progressof science and technology skills